Local Government Role in the Development of Industry Cluster based Tourism - Ika Sartika (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2017)
Ciwidey is one of tourism object in South Bandung that has various tourism products. Some are have similar product offerings, such as hot springs in Ciwalini amd Cimanggu. In practice, there is a competition among the similar attraction, so there are some attractions tend to lag behind compared to other attractions, and vice versa. Furthermore, it indicates there is no integrated strategy to develop Ciwidey as a tourism area. Existing strategies were only partial of each attraction. This leads to the benefits received by the community, administrators, and local governments have not optimal. There have been many studies about the tourism development strategy of Ciwidey made by various parties including the private sector would also academics. But until now integrated strategy for developing tourism area of Ciwidey is still relatively inconsiderable. One approach that can show the relationship among business actors are integrated industrial cluster approach. Industry cluster is basically not an entirely new concept. However, in line with the changing times, the study of the concept/theory of empirical experience various parties evolve over time. Various definitions and concepts of industrial clusters can be found in the literature. The definition of industrial clusters in brief is: "Industry Cluster is a specific business group connected by the chain of creation/increase in value added, either through business or non-business relationship". This study aims: (1) To map the tourism industry cluster of Ciwidey tourism area, (2) To formulate the role of local government in the tourism industry cluster in the tourism area of Ciwidey. After conducting interviews with stakeholders, the study documentation, and observations at the study site, it can be done mapping stakeholders that can be grouped in core industries, industrial suppliers, supporting industries, related industries, and buyers, as well as supporting institutions ("non-industry "). The most prominent role of each stakeholder is to create innovation and coordination. For innovation and coordination needed integrator in the tourism industry cluster of Ciwidey, and the role as the integrator can be done by the Department of Tourism, Youth and Sports Bandung Regency.